Caracterização físico-química da polpa de juçara em pó por spraydrying - Santana, Audirene Amorim [UNESP]; De Oliveira, Rafael Augustus; Telis, Vânia Regina Nicoletti [UNESP] (My University, 2016)
This study was carried out to evaluate the effects of different mixtures of carrier agents (CA) (modified starch-MS plus whey protein concentrate-WPC or soy protein isolate-SPI) on the characteristics of microcapsules containing spray-dried jussara pulp powder. Four treatments, 30%CAC+17.5%MS:WPC, 17.5%CAC+30%MS:WPC, 30%CAC+17.5%MS:SPI and 17.5%CAC+30%MS:SPI, were evaluated, where CAC=carrier agent concentration (g carrier/g jussara pulp solids) and the proportions MS:WPC and MS:SPI indicate the grams of protein (WPC or SPI) per 100g of carrier. The solubility of the particles was not affected by the wall material, attaining average values of 78%. The concentration of 30%CAC+17.5%MS:WPC improved the bulk density and moisture content. WPC and SPI were shown to be good alternative secondary wall materials for jussara pulp, together with MS.
Physicochemical characterization of jussara pulp powder by spray-drying
Keywords: Euterpe edulis martius; Modified starch; Soy protein isolate; Spray drying; Whey protein concentrate